Prevalence of and factors associated with high atherogenic index among adults in Nairobi urban informal settlements: The AWI-Gen study - David Wambui; Shukri Mohamed; Gershim Asiki (Public Library of Science (PLoS), 2022)
Dyslipidemia is an important cardiovascular disease predictor. Atherogenic index of plasma (AIP), a ratio of triglycerides (TG) to high density lipoprotein (HDL) cholesterol has been deemed to be more informative as a cardiovascular disease predictor compared to using any single predictor. The aim of this study was to explore the factors associated with elevated atherogenic index among people living in low-income urban areas of Nairobi, Kenya. Data used in this study were obtained from a cross-sectional population-based study with 2,003 participants conducted in Nairobi as part of the Africa Wits-INDEPTH Partnership for Genomic Research, AWI-Gen). Sociodemographic, behavioral, and clinical characteristics were collected from the participants. AIP was derived from the log of TG/HDL cholesterol and categorized into low risk (AIP<0.1), intermediate risk (AIP = 0.1-0.24) and high risk (AIP >0.24). Fifty-four percent (54%) of the study participants were women and the mean age of participants enrolled in this study was 48.8 years. Twenty-nine percent (29%) of study participants had high or medium atherogenic risk. Men, HIV patients, individuals with self-reported uncontrolled diabetes and obese individuals were at higher atherogenic risk. We have identified modifiable risk factors which can be addressed to reduce dyslipidemia in this population. Longitudinal studies may help to precisely determine how these factors relate with cardiovascular diseases.